Kajian Karakteristik Keluarga dan Penerapan Kadarzi pada Keluarga Balita di Wilayah Tembalang, Kota Semarang - Rachma Purwanti (Universitas Islam Negeri Walisongo Semarang, 2021)
This study aims to identify the implementation of Kadarzi under five years old children family in Tembalang area, Semarang City based on family characteristics. This study uses a cross-sectional design with the type of survey research in 40 families. The variables include family characteristics and 5 Kadarzi. Data analysis includes univariate and bivariate analysis (Mann Whitney, Chi-square, and Fisher exact tests based on the fulfillment of test requirements). The 5 Kadarzi indicators have been implemented by 25% of families with under-five children in the Tembalang area, Semarang City. Another 75% of families have not whole applied the Kadarzi indicator. Father's education and mother's education had a correlation with Kadarzi's 5th indicator, which is supplement consumption accordingly its recommendation (p = 0.004 and p = 0.009). The family category according to per capita income relates to exclusive breastfeeding for 6 months (p = 0.05). Other family characteristics variables (mother's work status and family size) are not related to the 5 Kadarzi indicators. The implementation of 5 Kadarzi indicators is carried out by 25% of families with under-five children in the Tembalang area, Semarang City. The implementation of Kadarzi needs to be continuously optimized to achieve the optimal nutritional status of toddlers and families. Penelitian ini bertujuan untuk mengidentifikasi penerapan Kadarzi pada keluarga balita di wilayah Tembalang, Kota Semarang berdasarkan karakteristik keluarga. Penelitian ini menggunakan desain cross sectional dengan jenis penelitian survei pada 40 keluarga balita. Variabel penelitian meliputi variabel bebas yaitu karakteristik keluarga dan variabel terikat yaitu 5 indikator Kadarzi. Analisis data secara univariat dan bivariat digunakan uji Mann whitney, Chi square, dan Fisher exact berdasarkan pemenuhan syarat uji). Penerapan 5 indikator Kadarzi telah dilaksanakan oleh 25% keluarga balita di wilayah Tembalang, Kota Semarang. Sebesar 75% keluarga lainnya belum menerapkan indikator Kadarzi secara keseluruhan. Pendidikan ayah dan pendidikan ibu berhubungan dengan indikator ke-5 Kadarzi yaitu konsumsi suplemen sesuai anjuran (p=0,004 dan p=0,009). Kategori keluarga menurut pendapatan per kapita berhubungan dengan pemberian ASI eksklusif selama 6 bulan (p=0,05). Variabel karakteristik keluarga lainnya (status pekerjaan ibu dan besar keluarga) tidak berhubungan dengan 5 indikator Kadarzi. Penerapan 5 indikator Kadarzi dilaksanakan oleh 25% keluarga balita di wilayah Tembalang, Kota Semarang. Penerapan Kadarzi perlu terus dioptimalkan untuk mencapai status gizi balita dan keluarga yang optimal.